Co-application of charcoal and wood ash to improve potassium availability in tropical mineral acid soils - Paramisparam, Puvan; Haruna, Osumanu Ahmed; Omar, Latifah; Huck, Ywih Ch'ng; Johan, Prisca Divra; Hamidi, Nur Hidayah (Multidisciplinary Digital Publishing Institute, 2021)
Potassium (K) is a macronutrient required by plants for energy production, enzyme activation, formation of cell wall, production of protein, and photosynthesis. However, K in the soil solution is leached from the rhizosphere before it interacts with soil colloids because of the abundance of kaolinite clay minerals in mineral acid soils such as Ultisols and Oxisols. These soils are highly weathered, low in organic matter, low in pH, but high aluminium (Al), and iron (Fe) ions. As a result, K becomes unavailable for plants, and this affects crop production and farmers’ profitability. This problem has steered the attention to the application of amendments to minimise K loss. Animal manures, plant residues, and composts applications are some of the corrective measures taken to improve the K availability in tropical acid soils. However, there is dearth of information on co-application of charcoal and wood ash as soil amendments to improve the K availability and the changes they cause to the dynamic equilibrium of K in mineral acid soils. Hence, this review discusses the dynamics, availability of K, and proposed mechanisms involved when charcoal and wood ash are used to amend tropical acid soils. The optimisation and understanding of the role of charcoal and wood ash co-application as soil amendments have potential benefits to improve the K availability and physicochemical properties of mineral acid soils.